A comparison of outcomes in morbidly obese, obese and non-obese patients undergoing primary total knee and total hip arthroplasty. Issue 1 (February 2018) - Deakin, Angela H.; Iyayi-Igbinovia, Aghimien; Love, Gavin J.
Abstract: Background: Obesity is a growing public health issue with the prevalence of morbid obesity, (Body Mass Index (BMI) ≥ 40 kg/m 2 ) increasing. There is some evidence these patients have more peri- and post-operative complications and poorer outcomes when undergoing arthroplasty procedures. This audit aimed to determine and compare the outcomes of non-obese, obese and morbidly obese patients undergoing arthroplasty at our institution. Method: This was a retrospective audit of patients from our institution who had undergone total knee (TKA) or total hip arthroplasty (THA) in 2009. Data collected were: age, gender, BMI, length of stay (LOS), Oxford knee or hip score (OKS/OHS), satisfaction and complications up to two years post operation. Patients were divided into three groups: BMI < 30, BMI 30–40 and BMI > 40. Outcomes for each BMI group were compared. Results: 1014 TKA and 906 THA operations were included. When compared to obese and non-obese patients, morbidly obese patients undergoing TKA had a mean LOS one day longer, a mean OKS four points lower and higher rates of postoperative problems, 37% vs. 21%. For THA patients there was no difference in LOS, OHS score was two points lower for each increasing BMI category and postoperative problems increase from 25% for non-obese to 31% for obese and 38% for morbidly obese patients. Conclusion: These results will be useful in informing obese patients of their potential outcomes following TKA or THA. These patients can then make a more informed choice before proceeding with arthroplasty.